Europe 2020 Strategy and European Recovery - Hoedl, Erich (Problemy Ekorozwoju, 2011)
European Recovery and a turn into a “new economy” in Europe are hampered by the Washington Consensus and the large disparities between the Member States. Europe 2020 Strategy neglects both dimensions and continuous to apply the basic principles of economic policy of the Lisbon Strategy. Emerging global multi-polarity need a loosening from the dollar-dominated financial markets and a priority for strengthening the real economy in Europe. Instead of financial help packages the public financial expenditures should be addressed to the seven flagship initiatives of the Europe 2020 Strategy, which can level-off existing economic disparities. For this, the Currency Union needs to be complemented by a fiscal policy going far beyond the stronger economic governance proposed by Europe 2020. Europe has to raise a financial transaction tax and to allocate it by a system of fiscal federalism partly to economically weaker Member States. Installing legally more elements of a “transfer union” would strengthen European competitiveness.